Increasing the Regional Economic Groth through Small and Medium Entreprises - Hedwigis Esti Riwayati (Universitas Hayam Wuruk Perbanas, 2017)
This study aimed to analyze the influence of regional revenue, capital expenditures, labor and small and medium enterprises towards the regional economic growth in the Regencies in Sulawesi Island. This study uses a quantitative approach with secondary data obtained from the Central Statistics Agency. Based on the results of the panel data analysis using EViews 8.0 program processing tools, the results indicate that in partial local revenue, capital expenditures, labor, small and medium enterprises have significant positive effect on regional economic growth in the Regency/City of the island of Sulawesi. Another conclusion of the results in this research are feasible estimated regression model is used to explain the economic growth of the Regency/City of the island of Sulawesi.